Juegos de azar y casinos: la experiencia española y una sugerencia de debate doctrinal para Brasil - José Eugenio Soriano García; Cláudia Ribeiro Pereira Nunes (Revista Interdisciplinar de Direito, 2020)
The traditional approach to the Spanish gambling regulation has fallen traditionally whitin the scope of the two Codes: theCivil Code, which set up their limits, and the Penal Code, which defines the prohibited practices. But the modern approach to gambling and games of chance regulation is done from the Public Law, and in particular, the Administrative Law on the grounds of the public intervention on recreational practices linked with leisure and tourism. The general objective of this paper, which results from the joint analysis of scholars from Brazil (UVA) and Spain (UCM), is focused in gambling and casinos. Particularly, it analyses in short the Spanish experience, in order to allow a comparative study that can be useful to foster further doctrinal debates.